Mediating Roles of Stress, Anxiety, and Depression in the Relationship between Constipation and Sleep Quality among the Elderly: Structural Equation Modeling (SEM) - Shahab Papi; Azin Barmala; Zeynab Amiri; Ahmad Vakili-Basir; Maria Cheraghi; Elham Nejadsadeghi (Sleep Science, 2023)
Introduction Sleep quality is an important health index in the elderly. As age increases, changes occur in sleep quality leading to sleep disorders and recurrent complaints. Sleep quality management of the elderly requires identification of its determinants. The present study aimed to determine the mediating roles of stress, anxiety, and depression in the relationship between constipation and sleep quality among the elderly using structural equation modeling (SEM).